The making of child and adolescent psychiatrists in Australia and New Zealand. (August 2022) - Perkes, Iain E; Eggleston, Matthew; Jacobs, Brian; McEvoy, Prue; Fung, Daniel; Robertson, Paul G
Child and adolescent psychiatry has an opportunity to adapt alongside the advancements in medical knowledge, post-graduate training, epidemiological realities and clinical service models. Here, we are guided by the mental health needs of our community's young and their families in our review of child and adolescent psychiatry training in Australia and New Zealand. We recognise that training must respond to clinical demand and service reform while ensuring a range of clinical and educational experiences to deliver expectable competencies in order to produce child and adolescent psychiatrists that meet the communities' needs now and in the future. We argue that training programmes be subject to rigorous evaluation by embedding continuing cycles of improvement including regular review and international bench marking.